MENGIDENTIFIKASI TAHAP PERKEMBANGAN FISIK DAN MOTORIK ANAK DI SEKOLAH DASAR DAN IMPLIKASINYA PADA PROSES PEMBELAJARAN - Arya Dani Rushertanto; Nuryati; Anfa Muarif Wicaksana; Darsinah; Murfiah Dewi Wulandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
Children's physical and motor development is an important factor that influences the success of the learning process in elementary schools. This study aims to identify the stages of physical and motor development of fifth-grade students at SDN 1 Bendosari Boyolali and analyze its implications for the learning process. A descriptive qualitative approach with a case study design was used to collect data through observation, interviews with teachers, and document analysis. The results of the study show that most students have reached the stage of gross motor development appropriate for their age, although some students experience delays in aspects of physical strength and flexibility. These differences in motor development impact the students' ability to participate in lessons requiring physical skills, such as physical education, arts, and academic skills that involve hand-eye coordination.